Transformation of the Role of Accountants in the Digital Era: A Literature Review on the Impact of Data Analytics in Financial Reporting - Yusi Sopianti; Susan Lalenoh; Yanuar Ramadhan (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the utilization of data analytics in financial reporting and examine the shift in the role of accountants in the digital era. Using the Systematic Literature Review (SLR) method, this study reviews scholarly articles from Google Scholar and Scopus published between 2020 and 2025, with sampling conducted in April 2025. The result of this paper stated that data analytics may improve the accuracy, transparency, and timeliness of financial reporting. Also, the role of accountants has transformed from merely recording transactions to becoming strategic analysts with multidisciplinary expertise in data analysis and technology. Adopting data analytics faces challenges such as data security, competency gaps, and internal resistance.